On the convergence of solutions of certain inhomogeneous fourth-order differential equations - Tunç, E. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The main purpose of this paper is to give sufficient conditions for the convergence of solutions of a certain class of fourth-order nonlinear differential equations using Lyapunov’s second method. Nonlinear functions involved are not necessarily differentiable, but a certain incrementary ratio for a function h lies in a closed subinterval of the Routh–Hurwitz interval.